Vyriešte (x + 1) (x + 3) (x + 4) (x + 6) = 112?

Vyriešte (x + 1) (x + 3) (x + 4) (x + 6) = 112?
Anonim

odpoveď:

# X = -7/2 + -isqrt31 / 2 # alebo # X = -7/2 + -sqrt57 / 2 #

vysvetlenie:

Poďme skupina LHS as

# (X + 1) (x + 6) (x + 3) (x + 4) = 112 #

# => (X ^ 2 + 7x + 6) (x ^ 2 + 7x + 12) = 112 #

Teraz nech # U = x ^ 2 + 7x # a potom vyššie uvedená rovnica

# (U + 6) (pri + 12) = 112 #

alebo # U ^ 2 + 18U + 72 = 112 #

alebo # U ^ 2 + 18U-40 = 0 #

alebo # (U + 20) (U-2) = 0 # tj. # U = 2 # alebo #-20#

Ako taký # X ^ 2 + 7x + 20 = 0 # tj. #X = (- 7 + -sqrt (7 ^ 2 až 80)) / 2 # tj. # X = -7/2 + -isqrt31 / 2 #

alebo # X ^ 2 + 7x-2 = 0 # tj. #X = (- 7 + -sqrt (7 ^ 2 + 8)) / 2 # tj. # X = -7/2 + -sqrt57 / 2 #